(untitled) (Docentes 2.0 Journal, 2021)
The university is a community of interests where educational processes are their core emerging actions within their institutional dynamics. The technification of the educational process has been going on for more than a decade, but it has had a dizzying growth in the last two years due to the CODIV-19 pandemic. Therefore, the research objective was to interpret the experiences of professors from the Yacambú University on university social responsibility (USR) in education mediated by technologies associated with the COVID-19 pandemic. In this sense, this carried research was out under a qualitative approach of an interpretive paradigm. The epistemological plane was assumed from social constructionism to understand the meanings that emerged from the dialogical exchange between the researcher and key informants, all with the support of the phenomenological-hermeneutical method. The sample is based on the archiving of opinions of 4 professors assigned to the Faculty of Humanities of the Yacambú University with functions of teaching, research, extension, management. As a finding of this research, it was obtained that universities are institutions of great relevance for the social development of a nation since they respond to the needs of populations, attending to emerging problems resulting from an investigative activity, thus managing to vindicate their role of social responsibility. Likewise, it was concluded to determine the importance of the technological aspect for a consolidation of the teacher and student in their current context.